Pembagian Harta Perkawinan Dalam Adat Masyarakat Mandailing Natal (suatu Kajian Antropologi Sosiologi hukum Islam) - Lubis, zulpahmi (AS-SAIS (JURNAL HUKUM TATA NEGARA/SIYASAH), 2023)
This research is motivated by the many conflicting understandings of the community about marital property and its distribution, especially to the Mandailing indigenous people. This research was conducted to examine the distribution of marital assets in the Mandailing community along with the factors behind it and analyzed by the Marriage Law and compilation of Islamic Law (KHI). This research is a juridical empirical research which is described in a qualitative descriptive using a case approach. The results of this study indicate that the distribution of marital assets to the Mandailing community is only done in cases of divorce. Meanwhile, in the case of one husband and wife died, the distribution of joint assets was not carried out. This means that the widow / widower only gets a share of the inheritance and does not receive the marriage assets. The factors behind the distribution of such marital assets in the Mandailing community are the influence of cultural customs that are still practiced today and the exemplary role of Malimkampung / Hatobangon. Although the distribution of marital assets to the Mandailing community is different from the provisions of the legislation and KHI, it is not said to be a violation of the law. Key words: Custom, Marriage Assets, Distribution, Mandailing Natal Penelitian ini dilatarbelakangi banyaknya simpang-siur pemahaman masyarakat terhadap harta perkawinan dan pembagiannya khusunya pada masyarakat adat Mandailing. Penelitian ini bertujuan untuk mengkaji pembagian harta perkawinan pada masyarakat Mandailing beserta faktor-faktornya yang dianalisa dengan menggunakan Undang-Undang dan Kompilasi hukum Islam. Penelitian ini merupakan penelitian Yuridis Empiris yang diuraikan dengan deskriptif kualitatif dengan menggunakan pendekatan kasus (case Opprouch). Hasil penelitian ini menununjukkan bahwa pembagian harta perkawinan pada masyarakat Mandailing hanya ada pada kasus cerai hidup. Sedangkan dalam kasus cerai mati (salah satu pasangan suami istri meninggal) pembagian harta bersama tidak dilakukan terhadap pasangan yang lebih lama hidup. Faktor yang melatarbelakangi pembagian harta perkawinan seprti demikian pada masyarakat mandailing adalah pengaruh adat budaya yang masih diamalakan sampai sekarang dan ketauladanan malimkampung/ hatobangon. Meskipun pembagian harta harta perkawinan pada masyarakat Mandailing berbeda dengan ketentuan perundang-undangan dan KHI, namun tidaklah dikatakan sebagai sebuah pelanggaran hukum.  Key word: Adat, Harta Perkwinan, Pembagian, Mandailing Natal